Allied Systems: Data governance challenges and the opioid crisis. Issue 1 (1st May 2022) - McDermott, Kevin
This teaching case based on real people and events describe a critical decision point during the nascent stage of entrepreneurial venture called Allied Systems Integration Solutions in May 2019. This data governance case explores the challenges with centralizing client data in an effort to help health practitioners cope with the opioid use crisis. Readers are asked to put themselves into the shoes of the protagonists who must make difficult operational decisions related to these data governance and behaviour management questions. This case is derived from participant observation of eight entrepreneurial mentoring sessions with the protagonist entrepreneurs. Detailed notes of participant observation sessions were maintained and qualitative data were analysed for the purpose of creating this business case. This case is intended for upper year undergraduate, or MBA courses. In particular, it should be used in curricula exploring the complexities of real-world data governance decisions, managing the trade-offs between operational efficiencies and data protection. This case would be most suited to courses in Management Information Systems, Database Management and Operations Management.